Early ultrasound-guided drainage of tubo-ovarian abscesses versus conservative treatment: a retrospective cross-sectional study - Vicente S Antonello; Suelyn Cristina P Ramos; Mirela F Jimenez; Felipe F Bassols (Journal of Infection in Developing Countries)
Objective: To compare the short and long-term benefits (the length of hospital stay, surgical complications, and early clinical improvement) of adding early ultrasound-guided drainage to broad-spectrum antibiotic treatment.